New partners of TKS4 scaffold protein - Kropyvko, S.V. (Вiopolymers and Cell, 2015)
TKS4 scaffold protein is involved in the formation of invadopodia, the production of reactive oxygen species (ROS) by tumor cells and other cellular processes. Aim. To identify new TKS4 partners involved in the actin cytoskeleton rearrangements and endo-/exocytosis. Methods. The GST pull-down assay was used to identify the interaction. Results. We revealed that TKS4 SH3 domains interact with the actin cytoskeleton reorganization proteins N-WASP and CR16, as well as with DNM2, SYNJ1 and OPHN1 which are involved in endo-/exocytosis. We also tested the WIP, WIRE, SHIP2, RhoU, RhoV and NUMB proteins, but their interaction with the SH3 domains of TKS4 was not found. Conclusions. The SH3 domains of TKS4 interact with N-WASP, DNM2, SYNJ1, OPHN1 and weakly with CR16 in vitro. Скафолд TKS4 бере участь у формуванні інвадоподій, продукції активних форм кисню (ROS) в ракових клітинах та інших клітинних процесах. Мета. Ідентифікувати нових партнерів TKS4, задіяних в перебудовах актинового цитоскелету та ендо-/екзоцитозі. Методи. In vitro GST pull-down assay. Результати. Показано, що SH3 домени TKS4 взаємодіють з білками-реорганізаторами актинового цитоскелету N-WASP та CR16, а також з DNM2, SYNJ1 та OPHN1, які задіяні в ендо-/екзоцитозі. Проте взаємодії WIP, WIRE, SHIP2, RhoU, RhoV та NUMB, з SH3 доменами TKS4 не знайдено. Висновки. SH3 домени TKS4 взаємодіють з білками N-WASP, DNM2, SYNJ1, OPHN1 та слабко з CR16 in vitro. Скаффолд TKS4 принимает участие в формировании инвадоподий, продукции активных форм кислорода (ROS) в раковых клетках и других клеточных процессах. Цель. Идентификация новых партнеров TKS4, участвующих в перестройках актинового цитоскелета и эндо-/экзоцитозе. Методы. In vitro GST pull-down assay. Результаты. Показано, что SH3 домены TKS4 взаимодействуют с белками-реорганизаторами актинового цитоскелета N-WASP и CR16, а также с DNM2, SYNJ1 и OPHN1, которые задействованы в эндо-/экзоцитозе. Взаимодействия WIP, WIRE, SHIP2, RhoU, RhoV и NUMB, с SH3 доменами TKS4 не выявлено. Выводы. SH3 домены TKS4 взаимодействуют с белками N-WASP, DNM2, SYNJ1, OPHN1 и слабо с CR16 in vitro.